Social Changes In Uzbekistan Agriculture In The First Half Of The 20th Century (The Example Of Kashkadarya) (Texas Journal of Philology, Culture and History, 2026)
This article studies the social and economic transformations carried out by the central government in rural areas of Kashkadarya region. In the course of the research, the impact of the policy of kulakization and collectivization on the lives of the rural population, as well as the contradictions that arose between social strata, are scientifically analyzed. The article also highlights the relations that have arisen in the social consciousness of the population as a result of the reduction of individual peasant farms, large land ownership and the distribution of private land resources. The results of the research are aimed at analyzing from a deep scientific perspective how rural life is changing socio-economically and the complex impact of these processes on local lifestyles